Analisis Tradisi Larangan Perkawinan Anak Pertama dan Ketiga (Lusan) dalam Perspektif Hukum Islam - Trisnayana, Wahida Emisa (TSAQOFAH, 2026)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife to establish a family characterized by sakinah, mawaddah, wa rahmah. However, in the modern era there remains the tradition of prohibiting marriages between first and third children (lusan), which persists as a living cultural practice within society, particularly in the Ponorogo region. This tradition is believed to preserve household harmony and avert misfortunes thought to befall the family, yet in practice it often becomes problematic when examined in light of Islamic law, which upholds the principles of freedom in choosing a spouse, justice, and maslahah (public welfare). This study aims to analyze the tradition of the lusan marriage prohibition from the perspective of Islamic law by examining dalil syar‘i, fiqhiyyah legal maxims, and the ʽurf approach as one of the sources of legal reasoning. The research employs a qualitative method with a normative-empirical approach through literature study and field observation to examine the position of the lusan tradition within the broader framework of the relationship between custom and sharīʿah. This study is expected to provide an analytical basis for formulating a proportional legal stance toward the lusan marriage prohibition tradition, thereby achieving a synthesis that respects local wisdom without neglecting the fundamental principles of Islamic law.